2009
DOI: 10.1021/ac9017583
|View full text |Cite
|
Sign up to set email alerts
|

Highly Specific Capture and Direct MALDI MS Analysis of Phosphopeptides by Zirconium Phosphonate on Self-Assembled Monolayers

Abstract: The dynamic range and low stoichiometry of protein phosphorylation frequently demands the enrichment of phosphorylated peptides from protein digests prior to mass spectrometry. Several techniques have been reported in literature for phosphopeptide enrichment, including metal oxides such as TiO(2) and ion metal affinity chromatography (IMAC). While the metal oxides have been used with reasonable success, IMAC has suffered from reduced selectivity and poor reproducibility. In this report, we present the first de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…Numerous studies have shown that ZrO 2 NPs have strong affinity to OP pesticides (Liu et al, 2008;Du et al, 2008a,b), phosphoric peptides (Hoang et al, 2010;Kweon and Håkansson, 2006) through chelation with phosphoric group. Motivated by these results, ZrO 2 NPs were employed here as capture reagent to recognize phosphorylated AChE.…”
Section: Principle Of Nanoparticles-based Immunosensor For Op-achementioning
confidence: 99%
“…Numerous studies have shown that ZrO 2 NPs have strong affinity to OP pesticides (Liu et al, 2008;Du et al, 2008a,b), phosphoric peptides (Hoang et al, 2010;Kweon and Håkansson, 2006) through chelation with phosphoric group. Motivated by these results, ZrO 2 NPs were employed here as capture reagent to recognize phosphorylated AChE.…”
Section: Principle Of Nanoparticles-based Immunosensor For Op-achementioning
confidence: 99%
“…It is inorganic oxide, whose band gap estimates from 5 to 7 eV [17,18] depending on the phase (cubic, tetragonal, monoclinic, or amorphous) and preparation methods. Researchers have also demonstrated that ZrO 2 has a strong affinity to negatively charge moieties [19], which motivated us to use graphene oxide (GO)-ZrO 2 nanocomposite as selective photocatalyst for heavy metals. Moreover, various papers have been published recently on the graphene-ZrO 2 nanocomposites applications, which include the deoxyribonucleic acid sensing detection [20], organophosphorus agents [21], supercapacitor energy-storage application [22], and photocatalytic degradation of antimonite (Sb(III)) and antimonate (Sb(V)) from aqueous solution [23].…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Many different analytical techniques have been developed to specifically enrich phosphopeptides including Immobilised Metal Affinity Chromatography (IMAC), utilizing iron, gallium, and more recently titanium and zirconium. [15,18,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] The efficiency of each of these metals in selectively binding phosphopeptides has been extensively investigated many times with varying success. This has been attributed to the non-specific binding of the acidic amino acid residues asparagine and glutamine to the metal ions, the binding of hydrophobic residues to the gel bed and the elution of multiply phosphorylated peptides and impurities in the metal oxide material.…”
Section: Introductionmentioning
confidence: 99%